Body Mass Index and Surgical Diagnosis of Endometriosis: Do Obese Patients Experience an Operative Delay? - Melissa A. Markowitz; Molly Doernberg; Howard J. Li; Yonghee K. Cho (Wolters Kluwer Medknow Publications, 2024)
Objectives: The objective of this study was to quantify the time to diagnosis of endometriosis by laparoscopy for patients of varying body mass index (BMI), as well as the safety of laparoscopy for endometriosis by BMI. Materials and Methods: We performed a retrospective cohort study of reproductive-age women receiving a primary laparoscopic diagnosis of endometriosis at an academic tertiary hospital from January 2017 to December 2020. Patients excluded were those undergoing repeat laparoscopy, with previously histologically diagnosed endometriosis, asymptomatic endometriosis, an unknown first gynecologic encounter, or an unknown initial BMI. Our primary outcome was time to surgical diagnosis of endometriosis by BMI class. Our secondary outcome was the evaluation of peri/postoperative risk of laparoscopy for endometriosis. Results: A total of 152 patients received a primary surgical diagnosis of endometriosis, including 44% normal or underweight patients, 29% overweight patients, and 27% obese patients. Obese patients experienced a delay from gynecologic presentation to diagnostic laparoscopy (18.4 months, interquartile range [IQR] 3.1-42.8) compared to overweight patients (9.0 months, IQR 2.5-23.2) and normal and underweight patients (3.8 months, IQR 1.1-17.0) (P = 0.02). Although a higher percentage of overweight and obese patients was Hispanic and non-Hispanic Black, multiple linear regression maintained a significant relationship between time to surgery and BMI (P = 0.03). Perioperative and postoperative complications did not differ by BMI class. There were no differences in repeat laparoscopy for endometriosis within 3 years by BMI (P = 0.99). Conclusion: BMI is independently associated with time to surgical diagnosis of endometriosis in our retrospective study. Diagnostic laparoscopy appears safe in obese patients, without significant perioperative morbidity.